RIA SW DAN ARIEF MUHAMMAD VLOG SEBAGAI MEDIUM DISEMINASI INFORMASI DAN KREATIVITAS - Fitri Kartika Sari (Jurnal Pustaka Ilmiah, 2018)
The development of the internet has made it easier for people to get information,spread information, and work using social media. Vlog is one of the social mediathat can earn income if it is consistent in its use. This study aims to compare the wayof vloggers in delivering video blogs. This study used descriptive qualitative method.The results of this study indicate that the vlog made by Ria SW with Arief Muhammadhas different content where they are both vloggers who are looking for income byattracting people to see the videos they upload. Suggestions and recommendationsfrom this study are that anyone can disseminate their work to the wider community,besides earning income by uploading videos such as Ria SW and Arief Muhammad ifthe public wants to use the internet media well.